Cervical Spine Navigation and Enabled Robotics: A New Frontier in Minimally Invasive Surgery. Issue 3 (October 2021) - Lebl, Darren R.; Avrumova, Fedan; Abjornson, Celeste; Cammisa, Frank P.
Background : Robotic-assisted and computer-assisted navigation (CAN) systems utilization has been rapidly increasing in recent years. Most existing data using these systems are performed in the thoracic, lumbar, and sacral spine. The unique anatomy of the cervical spine maybe where these technologies have the greatest potential. To date, the role of navigation-enabled robotics in the cervical spine remains in its early stages of development and study. Purpose : This review article describes the early experience, case descriptions and technical considerations with cervical spine screw fixation and decompression using CAN and robotic-assisted surgery. Methods : Representative cervical cases with early surgical experience with cervical and robotic assisted surgery with CAN. Surgical set up, technique considerations, instrumentation, screw accuracy and screw placement were elevated and recorded for each representative cervical case. Results : Existing robotic assisted spine surgical systems are reviewed as they pertain to the cervical spine. Method for cervical reference and positioning on radiolucent Mayfield tongs are presented. C1 lateral mass, odontoid fracture fixation, C2 pedicle, translaminar, subaxial lateral mass, mid cervical pedicle, navigated decompression and ACDF cases and techniques are presented. Conclusion : In conclusion, within the last several years, the use of CANs in spinal surgery has grown and the cervical spine shows the greatest potential. Several robotic systems have had FDA clearance for use in the spine, but such use requires simultaneous intraoperative fluoroscopic confirmation. In the coming years, this recommendation will likely be dropped as accuracy improves.